Difference in Immature Reticulocyte Fraction Percentage between Moderate and Severe Anemia in Transfusion-Dependent Thalassemia - Rizki Andriyani; Delita Prihatni; Ida Parwati; Tiene Rostini (Faculty of Medicine, Universitas Padjadjaran, 2021)
Thalassemia is an inherited genetic disease caused by the disruption in globin chain synthesis. Inefective erythropoiesis in thalassemia leads to moderate to severe anemia, requiring routine blood transfusions. To evaluate erythropoiesis, immature reticulocyte fractions (IRF) can be measured using the hematology analyzer, avoiding the need of invasive bone marrow examination. The purpose of this study was to analyze the differences in the IRF percentage between moderate and severe anemia in transfusion-dependent thalassemia (TDT) patients. This was a cross-sectional comparative observational analytic study conducted at the Pediatric Thalassemia Clinic of Dr. Hasan Sadikin General Hospital Bandung in August–September 2020. The IRF was examined using the fluorescence flowcytometry method with whole blood sample added by EDTA anticoagulant. The statistical analysis used in this study was unpaired t-test and Mann Whitney’s test. Subjects were 93 TDT pediatric patients, consisting of 48 boys (52%) and 45 girls (48%). The majority (72%) of the patients had been diagnosed with thalassemia for more than 5 years with moderate anemia (40%) and severe anemia (60%). The median IRF percentage in moderate anemia was 6.4% (range 0-22.7) while the range in severe anemia was 11.7% (range 4.1–35.8), suggesting a statistically significant difference (p<0.001) in the IRF percentage between moderate and severe anemia in transfusion-dependent thalassemia patients. To conclude, the more severe the anemia experienced by a thalassemia patient is, the higher the percentage of IRF.